Are trainees working in obstetrics and gynecology confident and competent in the care of frail gynecological oncology patients?. Issue 12 (12th October 2020) - Owens, Gemma Louise; Sivalingam, Vanitha; Abdelrahman, Mohamed; Beirne, James P; Blake, Dominic; Collins, Anna; Davies, Rhianna; Dilley, James; Farquharson, Malcolm; Frimpong, Diana; Gomes, Nana; Hawco, Sarah; et al.
Abstract : Introduction: Older patients undergoing cancer surgery are at increased risk of post-operative complications, prolonged hospital stay, and mortality. Identification of frailty can help predict patients at high risk of peri-operative complications and allow a collaborative, multidisciplinary team approach to their care. A survey was conducted to assess the confidence and knowledge of trainees in obstetrics and gynecology regarding identification and management of peri-operative issues encountered in frail gynecological oncology patients. Methods: A web-based survey was distributed via the Audit and Research in Gynaecological Oncology (ARGO) collaborative and UK Audit and Research Collaborative in Obstetrics and Gynaecology (UKARCOG) . The survey on the management of frail peri-operative patients was disseminated to doctors-in-training (trainees) working in obstetrics and gynecology in the United Kingdom (UK) and Ireland. Specialty (ST1–7), subspecialty, and general practice trainees, non-training grade doctors, and foundation year doctors currently working in obstetrics and gynecology were eligible. Consultants were excluded. Study data were collected using REDCAP software hosted at the University of Manchester. Responses were collected over a 6-week period between January and February 2020. Results: Of the 666 trainees who participated, 67% (425/666) reported inadequate training in peri-operative management of frail patients. Validated frailty assessment tools were used by only 9% (59/638) of trainees and less than 1% (4/613) were able to correctly identify all the diagnostic features of frailty. Common misconceptions included the use of chronological age and gender in frailty assessments. The majority of trainees (76.5%, 448/586) correctly answered a series of questions relating to mental capacity; however, only 6% (36/606) were able to correctly identify all three diagnostic features of delirium. A total of 87% (495/571) of trainees supported closer collaboration with geriatricians and a multidisciplinary approach. Conclusions: Obstetrics and gynecology trainees reported inadequate training in the peri-operative care of frail gynecological oncology patients, and overwhelmingly favored input from geriatricians. Routine use of validated frailty assessment tools may aid diagnosis of frailty in the peri-operative setting. There is an unmet need for formal education in the management of frail surgical patients within the UK and Irish obstetrics and gynecology curriculum.